2015
DOI: 10.4196/kjpp.2015.19.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfonylureas Administered Centrally on the Blood Glucose Level in Immobilization Stress Model

Abstract: Sulfonylureas are widely used as an antidiabetic drug. In the present study, the effects of sulfonylurea administered supraspinally on immobilization stress-induced blood glucose level were studied in ICR mice. Mice were once enforced into immobilization stress for 30 min and returned to the cage. The blood glucose level was measured 30, 60, and 120 min after immobilization stress initiation. We found that intracerebroventricular (i.c.v.) injection with 30 µg of glyburide, glipizide, glimepiride or tolazamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…As expected we found that restraint stress causes upregulation of blood glucose level; these results are similar to our previous studies . In addition, immobilization stress causes increases in both plasma corticosterone and insulin levels; these findings are in line in part with previous studies (Kang et al 2015;Sharma et al 2015). Furthermore, in the present study, we found that supraspinal or spinal pretreatment with 5,7-DHT causes a downregulation of the blood glucose level in the immobilization stress model.…”
Section: Discussionsupporting
confidence: 82%
“…As expected we found that restraint stress causes upregulation of blood glucose level; these results are similar to our previous studies . In addition, immobilization stress causes increases in both plasma corticosterone and insulin levels; these findings are in line in part with previous studies (Kang et al 2015;Sharma et al 2015). Furthermore, in the present study, we found that supraspinal or spinal pretreatment with 5,7-DHT causes a downregulation of the blood glucose level in the immobilization stress model.…”
Section: Discussionsupporting
confidence: 82%
“…And also in our previous study, we similarly observed that the increase in the blood glucose level after acute IMO was accompanied by a rise in the plasma insulin level. The elevation of the insulin level appears to maintain a homeostatic regulation of the blood glucose in IMO (Sharma et al 2015). In an earlier reported study, supraspinally administration with histamine H3 receptor agonist (proxyfan) significantly decreases the glucose level compared with control mice (Henry et al 2011).…”
Section: Discussionmentioning
confidence: 87%
“…In previous studies, we and others have observed that blood glucose level is increased in various types of animal stress models [ 31 32 33 34 ]. It has generally been known that the hyperglycemic effect is induced by both physical and emotional stress.…”
Section: Discussionmentioning
confidence: 99%